Towards an annotated corpus of Soqotri oral literature: the 2010 fieldwork season - Naumkin, Vitaly; Kogan, Leonid; Cherkashin, Dmitry; ΚĪsā ad-DaΚrhī, AΉmad; ad-DaΚrhī, ΚĪsā GumΚān (Proceedings of the Seminar for Arabian Studies, 2012)
At the Seminar for Arabian Studies in 2011,1 had the pleasure of introducing 'Towards an annotated corpus of Soqotri oral literature' on behalf of Vitaly Naumkin and his colleagues. Recently, there has been a significant increase in fieldwork and documentation of Modern South Arabian languages, in particular Soqotri (thanks to work by Naumkin, Kogan and their colleagues, and Morris), and Mehri. This has included the publication of new sets of oral texts, including Stroomer (1999), Sima (2009), Liebhaber (2011), and Morris & Di-Kishin (in preparation). Where they deal with cultural issues covered by the early twentieth-century work of the Viennese Expedition, these new publications may shed significant light both on the historical development of the languages and on cultural change. As pointed out by the authors here, however, the majority of published Modern South Arabian folklore texts lack linguistic and cultural annotations, and this lack of annotation makes it difficult for both Semitists and typological linguists to exploit this data source properly for comparative purposes. This paper by Naumkin et al. suggests and exemplifies an approach to increase the accessibility and usability of the material: the two Soqotri folklore texts here are presented in phonological transcription, English and Arabic translations, an orthographic transcription in Arabic-based script developed by c Isä Gum c än al-Da c rhï, and detailed linguistic and cultural notes. For single texts and shorter text collections, annotations should be provided where possible; and while space considerations in paper-based publications may preclude the use of detailed annotations in longer sets of texts, online publication methods can be exploited since they suffer from no such constraints.